The interplay among intraspecific leaf trait variation, niche breadth and species abundance along light and soil nutrient gradients. Issue 6 (8th February 2019) - Fajardo, Alex; Siefert, Andrew
Abstract : It is assumed that widespread, generalist species have high phenotypic variation, but we know little about how intraspecific trait variation (ITV) relates to species abundance and niche breadth. In the temperate rainforest of southern Chile, we hypothesized that species with wide niche breadth would exhibit 1) high among‐plot ITV, 2) a strong relationship between trait values and the environment, and 3) a close fit between traits and local environment trait optima. We measured leaf functional traits (leaf area, LMA, leaf N and P concentrations) of saplings in woody species, and compared the relative abundance of each species with its niche breadth, measured as the range of light, soil N and P availability. We used the slope of the linear regression of species' trait–environment relationships to assess the strength and direction of these relationships, and measured the degree to which species' trait values track the environmental optimum across plots. In some cases, species having wide niche breadth had high ITV in leaf N and also matched traits (LMA and leaf P) to local optima along the light gradient; they also had high ITV in general and matched leaf P to local optima along the soil P gradient. The relationship between species with wide niche breadth and the strength of intraspecific trait–environment relationships was generally weak and varied depending on the niche dimension and trait in question. Species varied considerably in the strength of trait–environment relationships and total magnitude of ITV, and this variation was not generally strongly related to species abundances or niche breadth patterns. In conclusion, trait variation at the community level is not driven by a few abundant, widely distributed species, but depends on the aggregate trait responses of both abundant and rare species. This makes it difficult to scale individual species trait responses up to the community level.